2005
DOI: 10.1177/15257401050260030301
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to Improve Expressive Grammar for Adults With Down Syndrome

Abstract: Recent investigations have supported the ability of persons withDown syndrome to continue learning language on into adulthood. The importance of intervention to increase communicative competence is evident-what is not known is the effectiveness of such intervention. The authors report here on a series of case studies that investigated a language intervention that targeted syntax for adults with Down syndrome. The intervention used a hybrid approach combining naturalistic intervention contexts with structured e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…In fact, OCs for grammatical morphemes are usually very infrequent in spontaneous language samples (Balason and Dollaghan 2002), making estimates extremely unreliable 6 . Furthermore, Hewitt et al (2005) comment on the difficulty of determining OCs in conversation and report their percentage coder agreement as 67%. In short, even though use of a measure of OCs would facilitate comparison with earlier studies, its methodological problems render its applicability suspect for analysing conversation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, OCs for grammatical morphemes are usually very infrequent in spontaneous language samples (Balason and Dollaghan 2002), making estimates extremely unreliable 6 . Furthermore, Hewitt et al (2005) comment on the difficulty of determining OCs in conversation and report their percentage coder agreement as 67%. In short, even though use of a measure of OCs would facilitate comparison with earlier studies, its methodological problems render its applicability suspect for analysing conversation.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many studies have pointed out syntactic deficits in specific language impairment (SLI) (Bedore and Leonard 1998, Eadie et al 2002), Down's syndrome (Abbeduto and Chapman 2005, Eadie et al 2002), and high‐functioning autism (HFA) (Landa and Goldberg 2005, Roberts et al 2004). Syntax is important, lastly, because improvements in this area translate into improvements in general communication abilities and into better perceptions of individuals with disabilities (Hewitt et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, syntactic difficulties have an enormous impact on the daily living of individuals with disabilities (Hewitt, Hinkle, & Miccio, 2005). Recent studies have demonstrated weaknesses in expressive syntax in fragile X syndrome (FXS) as well (Estigarribia, Roberts, Price, & Sideris, 2010; Roberts, Hennon, Price, Dear, Anderson, & Vandergrift, 2007; Price, Roberts, Hennon, Berni, Anderson, & Sideris, 2008).…”
Section: Cognitive Environmental and Linguistic Predictors Of Syntamentioning
confidence: 99%
“…This was one aim that our colleague, Adele Miccio made a priority as part of her contributions to the field. The willingness and interest in explaining diagnostic and treatment innovations to practicing clinicians is clearly demonstrated in the breadth of Miccio’s work, which encompassed, for example, phonological disorders (Miccio and Ingrisano, 2000; Miccio, 2002; 2005), stimulability (Miccio and Elbert, 1996), otitis media (Miccio, Yont, and Vernon-Feagans, 2002), bilingualism (Miccio, Hammer, and Toribio, 2002), Down’s syndrome (Hewitt, Hinkle, and Miccio, 2005), specific language impairment (Yont, Miccio, and Hewitt, 2002), literacy (Hammer and Miccio, 2004), and pragmatics (Vernon-Feagans, Miccio, and Yont, 2003). …”
Section: Introductionmentioning
confidence: 99%